2018
DOI: 10.1093/mnras/sty1071
|View full text |Cite
|
Sign up to set email alerts
|

The architecture and formation of the Kepler-30 planetary system

Abstract: We study the orbital architecture, physical characteristics of planets, formation and long-term evolution of the Kepler-30 planetary system, detected and announced in 2012 by the KEPLER team. We show that the Kepler-30 system belongs to a particular class of very compact and quasi-resonant, yet long-term stable planetary systems. We re-analyse the light curves of the host star spanning Q1-Q17 quarters of the KEPLER mission. A huge variability of the Transit Timing Variations (TTV) exceeding 2 days is induced b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 97 publications
1
19
0
Order By: Relevance
“…This system hosts two confirmed giant planets and a smaller confirmed super-Earth-sized planet called Kepler-30 b, which orbits with a period of 29.16days (Fabrycky et al 2012). All of these planets show TTVs, and Kepler-30 d shows extremely large TTVs with an amplitude of more than a day (Fabrycky et al 2012;Panichi et al 2017 Four of these new TCEs were predicted to be planets by our model with a probability of 0.9 or greater. We consider this to be a very confident prediction; among those objects in our test set to which our model assigned a planet probability greater than 0.9, 96% turned out to be correctly classified as planets.…”
Section: Summary Of New Highly Ranked Tcesmentioning
confidence: 86%
“…This system hosts two confirmed giant planets and a smaller confirmed super-Earth-sized planet called Kepler-30 b, which orbits with a period of 29.16days (Fabrycky et al 2012). All of these planets show TTVs, and Kepler-30 d shows extremely large TTVs with an amplitude of more than a day (Fabrycky et al 2012;Panichi et al 2017 Four of these new TCEs were predicted to be planets by our model with a probability of 0.9 or greater. We consider this to be a very confident prediction; among those objects in our test set to which our model assigned a planet probability greater than 0.9, 96% turned out to be correctly classified as planets.…”
Section: Summary Of New Highly Ranked Tcesmentioning
confidence: 86%
“…The stable chaos scenario suggested by Deck et al (2012) completely overlaps with the stickiness effect appearing at the border of regular domains (MMRs in celestial mechanics) in dynamical systems (Tsiganis et al 2000). In addition, Panichi et al (2018) also found that the system (Kepler-36) is very close to the border of the 7:6 MMR.…”
Section: Two-planet System: Kepler-36mentioning
confidence: 69%
“…Thus one should handle the analysis with care. (Panichi et al 2018) showed that the integration time plays an important role in the stability investigation of this particular systems. Although, the initial conditions of the inner planet (Kepler-29b) are sitting well inside the regular domain of the (a, e) stability map for shorter time, it turns out that the center of the resonance becomes unstable for longer integration.…”
Section: Two-planet System: Kepler-29mentioning
confidence: 97%
See 1 more Smart Citation
“…TOI-201 b also joins the small but growing population of longer-period giant planets, helping to populate a still relatively sparse region of the radius-period diagram (Figure 10). On this diagram, it is located closest to Kepler-117 c (period 50.790391 ± 0.000014 days, radius 1.101 ± 0.035 R J , mass 1.84 ± 0.18 M J , eccentricity 0.0323 ± 0.0033; Bruno et al 2015) and Kepler-30 c (period 60.32503 ± 0.00010 days, radius 1.069 ± 0.025 R J , mass 1.686 ± 0.016 M J , eccentricity 0.0115 ± 0.0005; Panichi et al 2018) but is noticeably less massive and dense, and more eccentric, than both these planets. Given the relative youth of the TOI-201 system, with a stellar As noted in the introduction, the size and mass of warm Jupiters is determined by their metallicity.…”
Section: Discussionmentioning
confidence: 99%